Accountability Zakat Fund Management Based on Trust Metaphor in Improving Good Zakat Governance (Case Study of the National Zakat Collection Agency of the Regency of Gowa) - Opi Asrika; Lince Bulutoding; Muhammad Sapril Sardi Juardi (Journal of Applied Taxation and Policy, 2026)
This study aims to analyze the accountability of zakat fund management at the National Zakat Agency (BAZNAS) of Gowa Regency and to examine the role of the amanah (trust) metaphor in enhancing good zakat governance . This qualitative research uses a case study approach, with data obtained through interviews, observation, and documentation involving BAZNAS officials, zakat payers (muzakki), and recipients (mustahik). The data were analyzed through data reduction, presentation, and conclusion drawing. The results show that accountability practices at BAZNAS Gowa are reflected in transparent reporting, timely fund distribution, clear policy targets, and effective financial control. The application of amanah values such as honesty and fairness strengthens these practices and supports the principles of transparency, responsibility, accountability, and independence. This study concludes that integrating trust into zakat management can foster professionalism, public trust, and equitable distribution, thereby improving the overall quality of zakat governance.